Ideal profile of the 21st century teacher (Research, Society and Development, 2021)
Speaking of education today is almost impossible not to mention the countless changes that have taken place over the years, which have demanded an extra effort from those who make it happen “the teacher”. The teacher often needs to reinvent himself in order to be able to accompany a society in daily transformations and all these transformations, especially in the educational field, have generated concerns in the search for a better quality in the teacher's relationship with the teaching-learning process. Teaching today is a challenge of gigantic proportions, it has much more to do with the education of the citizen than with the transmission of ready and finished content, I believe that this has been the main change in the educational field when we refer to teaching practice. But after all, what should the 21st century teacher has to fit into this new model of society? Reading this article will allow a reflection on this ideal teacher profile.